2019
DOI: 10.29333/ejgm/114664
|View full text |Cite
|
Sign up to set email alerts
|

Compulsive gaming in secondary school students from five Peruvian cities: Usage and addiction to the Pokémon GO game

Abstract: Introduction: Some years ago, the Pokémon GO game became incredibly popular. However, no studies on the subject have been conducted in Peru involving vulnerable populations, such as adolescents. Objective: To determine if the number of hours playing the Pokémon GO game is associated with Internet and/or video game addiction, as well as to other factors in secondary school students from five Peruvian cities. Materials and methods: Cross-sectional, analytical, and multi-centric study, with a sample of 944 school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 15 publications
0
18
1
1
Order By: Relevance
“…The current study sample had a mild level of IA, which is inconsistent with Guo and colleagues' findings that universitylevel students had moderate to severe levels of IA among university-level students [16]. In addition, it was found that 44% and 23% of students were addicted to the Internet and video games, respectively [39]. In the present study, students with experience of being online four years or under failed to cut down on the amount of time they spent online compared to students with over four years of experience.…”
Section: Internet Addiction (Ia)contrasting
confidence: 99%
“…The current study sample had a mild level of IA, which is inconsistent with Guo and colleagues' findings that universitylevel students had moderate to severe levels of IA among university-level students [16]. In addition, it was found that 44% and 23% of students were addicted to the Internet and video games, respectively [39]. In the present study, students with experience of being online four years or under failed to cut down on the amount of time they spent online compared to students with over four years of experience.…”
Section: Internet Addiction (Ia)contrasting
confidence: 99%
“…Of a total of 1567 potential records, 428 duplicate records were removed. In total, 1139 articles were evaluated by reviewing the title and abstract, and 24 passed to the full-text review phase [ 19 , 20 , 21 , 22 , 23 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Finally, six met the selection criteria and were included in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, six met the selection criteria and were included in the systematic review. Regarding the excluded articles, ten were not included because they did not report results on GD [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 52 ], five studies were excluded because they were instruments or validations of GD [ 23 , 43 , 44 , 45 , 46 ], two studies did not include the target population (LAC) [ 47 , 48 ], and one study was excluded because it had the same results as an already included study population [ 49 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The problem of cyberbullying is a serious problem for youth as the number of Internet users is growing every year (Yilmaz, 2010;Mejia et al, 2019;Mikhaylovsky et al, 2019;Tabachuk et al, 2018). A significant part of young people use smartphones (de Arriba Pérez et al, 2016;Park & Kim, 2018;Marques & Pitarma, 2016;Jeong, 2017).…”
Section: Review Of Literaturementioning
confidence: 99%